Three New Species of Tyloperla Sivec & Stark (Plecoptera: Perlidae) from India - Stark, Bill P. (Illiesia, 2014)
Three new species of Tyloperla Sivec & Stark are proposed from specimens collected in Karnataka, Maharashtra and Himachal Pradesh states, India. The new species are compared with other members of the genus, a key for species known from the Indian subcontinent is presented, and an updated checklist of Tyloperla species is given.
Keywords: entomology; stoneflies; Perlidae; Plecoptera; Tyloperla; new species; India